ANALISIS PENGELOLAAN USAHA BERBASIS SYARIAH PADA MASA COVID 19 - Burhanuddin Burhanuddin (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2020)
The purpose of this study is to describe sharia-based business management during the corona 19 pandemic. The data collection methods used were interviews and literature. The data analysis method is in the form of qualitative descriptive analysis. Based on the results of data analysis, the authors found that sharia-based business management during the 19 pandemic experienced a change in habits. From doing business that was not customary to use telecommunications technology and media before Covid 19, so they had to use it. In the sense of analyzing new business habits during the Covid 19 pandemic, it shows trends in the use of technology and telecommunications media, such as online business.